2020
DOI: 10.14744/eej.2020.38258
|View full text |Cite
|
Sign up to set email alerts
|

Smear Layer Removal from Root Canal Dentin and Antimicrobial Effect of Citric Acid-modified Chlorhexidine

Abstract: Objective: To study the effectiveness of various concentrations of citric acid (CA) added to 2% chlorhexidine (CHX) on smear layer removal from the root canal wall and antimicrobial efficacy against Enterococcus faecalis ( E. faecalis ) and Candida albicans ( C. albicans ). Methods: Fifty-three single-rooted mandibular premolars were decoronate and the root canals underwent mechanical instrumentation using MTwo rotar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Chlorhexidine is a broad-spectrum antiseptic effective against Gram-positive and negative bacteria, furthermore fungi. It is used in dentistry to control dental biofilms' growth and treat periodontitis or root canals, especially Enterococcus faecalis ( 18 , 19 ). At the latest since the COVID-19 pandemic, a pre-procedural mouth rinse with CHX is widely accepted in dentistry, although an antiviral effect in the oral cavity was unproven so far ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine is a broad-spectrum antiseptic effective against Gram-positive and negative bacteria, furthermore fungi. It is used in dentistry to control dental biofilms' growth and treat periodontitis or root canals, especially Enterococcus faecalis ( 18 , 19 ). At the latest since the COVID-19 pandemic, a pre-procedural mouth rinse with CHX is widely accepted in dentistry, although an antiviral effect in the oral cavity was unproven so far ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 27 ). In addition to this, after removing the smear layer by using a chelating agent, it is reasonable to irrigate the canal again with another disinfecting solution to attack the bacteria remaining in the dentin tubules ( 28 ). However, when NaOCl is used as a final disinfectant for this purpose, it shows the corrosive effect on the dentin microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…However, when NaOCl is used as a final disinfectant for this purpose, it shows the corrosive effect on the dentin microstructure. Therefore, using QMix as a single final solution and thus reducing disinfection steps can provide optimal final irrigation without dentin erosion caused by NaOCl ( 1 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Carisolv treatment, the smear layer was not removed completely from the cavity surface after citric acid and tartaric acid treatment, and smear layer and closed dentin microtubules were observed in several areas of the cavity surface. Previous papers suggested that root canal irrigation with 10% of citric acid enabled efficient removal of smear layer in root canal walls [23][24][25]. However, both 10% citric acid reagent and 10% tartaric acid reagent could not remove the smear layer completely.…”
Section: Discussionmentioning
confidence: 99%